Post-recovery health domain scores among outpatients by SARS-CoV-2 testing status during the pre-Delta period - Jennifer P. King; Jessie R. Chung; James G. Donahue; Emily T. Martin; Aleda M. Leis; Arnold S. Monto; Manjusha Gaglani; Kayan Dunnigan; Chandni Raiyani; Sharon Saydah; Brendan Flannery; Edward A. Belongia (BMC Infectious Diseases, 2024)
Abstract Background Symptoms of COVID-19 including fatigue and dyspnea, may persist for weeks to months after SARS-CoV-2 infection. This study compared self-reported disability among SARS-CoV-2-positive and negative persons with mild to moderate COVID-19-like illness who presented for outpatient care before widespread COVID-19 vaccination. Methods Unvaccinated adults with COVID-19-like illness enrolled within 10 days of illness onset at three US Flu Vaccine Effectiveness Network sites were tested for SARS-CoV-2 by molecular assay. Enrollees completed an enrollment questionnaire and two follow-up surveys (7–24 days and 2–7 months after illness onset) online or by phone to assess illness characteristics and health status. The second follow-up survey included questions measuring global health, physical function, fatigue, and dyspnea. Scores in the four domains were compared by participants’ SARS-CoV-2 test results in univariate analysis and multivariable Gamma regression. Results During September 22, 2020 – February 13, 2021, 2712 eligible adults were enrolled, 1541 completed the first follow-up survey, and 650 completed the second follow-up survey. SARS-CoV-2-positive participants were more likely to report fever at acute illness but were otherwise comparable to SARS-CoV-2-negative participants. At first follow-up, SARS-CoV-2-positive participants were less likely to have reported fully or mostly recovered from their illness compared to SARS-CoV-2-negative participants. At second follow-up, no differences by SARS-CoV-2 test results were detected in the four domains in the multivariable model. Conclusion Self-reported disability was similar among outpatient SARS-CoV-2-positive and -negative adults 2–7 months after illness onset.